Comment on “Between emptiness and reality: from the white space in Chinese painting to the philosophy of form in western art” - Ximing Xu (Trans/Form/Ação)
Commented article: WANG, L.; WANG, B. Between emptiness and reality: from the white space in Chinese painting to the philosophy of form in western art. Trans/Form/Ação: Unesp journal of philosophy, Marília, v. 48, n. 3, “Eastern thought”, e0250010, 2025. Available at: https://revistas.marilia.unesp.br/index.php/transformacao/article/view/16396.